Enhancing Operational Efficiency in Culinary MSMEs through Profit-Sharing Based Working Capital - Sarwono; Erwina Kartika Devi (Journal of Economics and Social Sciences (JESS), 2025)
Culinary MSMEs often face structural challenges regarding financial instability and rigid debt obligations that hinder operational growth. This study explores how profit-sharing based working capital enhances operational efficiency, using the cassava chip industry in Geragai District, Tanjung Jabung Timur, as a case study. Employing a qualitative case study design with purposive sampling, data were collected through in-depth interviews, field observations, and financial document reviews, then analyzed using thematic analysis. The results indicate that the profit-sharing model acts as a "financial safety valve," providing flexibility during raw material price surges and preventing production halts. Furthermore, the participatory monitoring inherent in partnership agreements reduces "cost leakage" and minimizes production waste, improving inventory spoilage from 8% to less than 3%. The study concludes that profit-sharing fosters a professional accounting culture and managerial discipline, offering a more resilient financial framework than traditional debt. These findings suggest that for culinary MSMEs, the structure of capital repayment is more decisive for sustainability than the mere volume of capital injected